Determinación de la composición química, propiedades físicas y evaluación de la actividad biológica del aceite esencial de Piper ecuadorense del cantón Saraguro - Flores Maza, Paola Katherine (2015)
The essential oil of Piper ecuadorense was obtained by hydrodistillation. The chemical composition of the essential oil was determined by gas chromatography coupled with mass spectrometry and the flame ionization detector The biological activity was evaluated by broth microdilution method and the antioxidant activity by two spectrophotometric methods: ABTS assay, and the DPPH method. Oil physical properties were also determined. Fifty-six compounds were identified representing 98.98 % of the essential oil. The most representative components were: α-Phellanderene (6,89%), δ-Elemene (6,83%), β Elemene (3,55%), α-Humulene (3,20%), Bicyclogermacrene (12,98%), δ-Cadinene (3,85%), (E)-Nerolidol (6,88%), Germacrene D-4-ol (5,04%), 3-Thujopsanone (11,59%), y Shyobunol (5,79%). The density was 0,9269 g/cm3 and the refractive index 1,5043. The essential oil presented a moderate microbial activity against Staphylococcus aureus (MIC 125 μg/mL), while other bacterial strains were not inhibited at the doses tested, with respect to fungi showed good activity against T. mentagrophytes (CMI 62,5μg / mL), and T. rubrum (CMI 31,5 ug/mL). The essential oil of this species do not showed antioxidant activity at various concentrations evaluated.